Wounded landscape: Environmental and social consequences of (illegal) motor tourism in forests on the example of Worek Okrzeszyna (the Central Sudetes on the Polish-Czech borderland) - Chylińska, Dagmara; Kołodziejczyk, Krzysztof (Quaestiones Geographicae, 2023)
Off-road vehicles (ORVs) have recently become a serious problem not only for natural peripheral areas, but also for those rare green enclaves in heavily urbanised regions. The consequences of motor traffic in naturally valuable areas, including forests, affect the environment together with all its users to different extent. The scale and ubiquity of this type of motor tourism in Poland convinced the authors to research the subject and assess its influence on the forest environment, on the example of the mountains surrounding the region called Worek Okrzeszyna on the Polish-Czech borderland. The authors aimed to determine the scale and character of the phenomenon in forests and environmentally valuable areas in Poland, as well as to assess its scope in the examined research area together with the environmental and social effects. A field inventory of all the trails used by motor tourists was carried out, with particular emphasis on the extent of the network and their environmental consequences. In the ranges surrounding Worek Okrzeszyna from the south, a significant negative impact of illegal motor tourism on the vegetation, soil and relief have been revealed. It occurs wherever the phenomenon takes place: on forest roads, tourist trails and beyond them. Although the main research subject is the pressure of motor tourism on the environment, the authors also raise questions regarding social consequences of the phenomenon (noise, worse aesthetic experience), followed by the limits of tourism as such.